ANALYSING THE USE AND FUNCTION OF LEXICAL COHESION IN THE SHORT STORY OF HOP FROG - Erwadi Erwadi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2017)
This study was aimed at analyzing the use of lexical cohesion and its function in Hop Frog, a short story written by Allan Edgar Poe. This qualitative research employed a documentation analysis to analyze the use and functions of lexical cohesions found in the short story. having analyzed the data, it was found that there are five general categories of lexical cohesion such as hyponymy, antonymy, repetition, synonymy, and meronymy of which the finding is in line with the kind of lexical cohesion proposed by Hassan’s theory. It was also found that the functions of each lexical cohesions consist of ideational, interpersonal, and textual function showing in each lexical cohesion of which they are the same as that of stated by Halliday’s theory.